The first-row transition metal-catalysed enantioconvergent radical Suzuki-Miyaura C(sp)-C coupling of racemic alkyl halides - Liu, Lin; Yang, Chang-Jiang; Li, Zhong-Liang; Gu, Qiang-Shuai; Liu, Xin-Yuan (Green chemistry : an international journal and green chemistry resource : GC, 2024)
The enantioconvergent radical Suzuki-Miyaura cross-coupling of racemic alkyl halides represents a powerful approach for the construction of valuable C(sp 3 )-C bonds. In this regard, the earth-abundant first-row transition metal (Ni, Fe, Co, and Cu) catalyst possesses a good single-electron transfer ability and can easily convert racemic alkyl halides to the prochiral alkyl radicals, providing an ideal solution for enantioconvergence. The utilization of chiral ligands would further facilitate the realization of enantioselective control over the prochiral alkyl radicals. This Perspective will discuss the advances and anticipate further development in this burgeoning field. This perspective highlights recent advances and provides an outlook on future developments in the first-row transition metal catalysed enantioconvergent radical Suzuki-Miyaura C(sp 3 )−C coupling of racemic alkyl halides.